Widening the gene pool of sexual tetraploid bahiagrass : generation and reproductive characterization of a sexual synthetic tetraploid population - Zilli, Alex Leonel (2018)
Fil: Zilli, Alex Leonel. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.